Mobility in Land Use Planning Tools - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The issue of the relation between transport and land use has been extensively debated, particularly during the last decades. The need for an integration of these two planning sectors is widely acknowledged even though this integration is still difficult to occur. Italy, as usually, seem to be very late as concerns urban and transport planning integration. As a matter of fact, Italian town planner are still engaged in affirming a “new urban plan” able to keep up with urban and territorial transformation process. This is why there is not yet a unique national law for urban and regional planning. Nevertheless, it is possible to find some examples in urban planning practices aimed at implementing integration between urban needs and transport development. This article try to point out how planning of mobility system has a central role in some recent master plan even though integration is still long to come. The case of Rome has been considered because of the historical context in which it has been carried out. Master Plan has been adopted only in 2008 after about ten years of debate and discussion. But this is not what this article intends to analyze. The case of Master Plan of Rome is probably the main “theoretical” example of integrating urban development and transport planning. It is theoretical because at present, despite some years have passed since its processing, car is still the most used mean for urban travel. The second case examined refers to Master Plan of Bologna. This has been grounded on a strategic approach leading to “seven different cities”. These visions have been all aimed at implementing soft mobility as mean of urban requalification. The last case refers to Milan and its Urban Government Plan recently proposed to the local administration adoption. This consists of three integrated documents (Document Plan, Plan Rules and Plan of Services) and defines the future asset of the city. This Master Plan is not yet in force but it has been considered relevant for this article goals. Large part of the Document Plan has been built on the idea of converting the original radial asset of the city. The mobility system planning refers to four different urban areas (north, south, east, west) and it is strictly connected to the Transformations Areas of the Master Plan. This Plan outlines an ambitious project of urban development mostly based on mobility system transformation. At present, there is no evidence on the success or failure of this project that is still in debate, anyway it represents an up-to-date case in Italian panorama of town planning. Finally, something are happening in Italian town planning, but it is still more theoretical than practice. The awareness that an effective integration requires new areas of interdisciplinary competencies, innovative practices and tools, is still weak. It asks for a collaborative government model and cooperative polices able to affect decision making process.